The public archaeology of treasure - Williams, Howard, 1972-; Reavill, Peter,; Clague, Samuel, (Access archaeology., 2022)
Select proceedings of the 5th University of Chester Archaeology Student Conference (31st January 2020) reflect on the shifting and conflicting meanings, values and significances for treasure in archaeology's public engagements, interactions, and manifestations.